ACTIVATION OF MARKETING COMMUNICATIONS OF JSC CONCERN GALNAFTOGAZ IN THE DIRECTION OF INCREASING ITS COMPETITIVENESS - Kosar , N. S.; Yarychevska , Ya. I. (The actual problems of regional economy development, 2023)
The modern market of light petroleum products in Ukraine is marked by a tendency to increase competition between filling station networks. In order to increase the competitiveness of sellers on it in conditions of non-price competition, it is important for them to successfully identify, develop and effectively implement various marketing communications tools. The article is aimed at developing proposals for improving the system of management of marketing communications of the operator in the market of light petroleum products of Ukraine on the basis of their analysis, developing a model for their management. Based on the analysis of competitiveness, it has been established that in order to ensure the constant interest of consumers in purchasing products in OKKO network, JSC "Concern "Galnaftogaz" needs to strengthen its positions in such areas as reputation (image potential), level of service, marketing efforts, in particular informing customers on the Internet. According to the results of the analysis of the websites of JSC "Concern "Galnaftogaz" and its two competitors - PUG "CONTINUUM" and PJSC "UKRNAFTA", it can be concluded that JSC "Concern "Galnaftogaz" should focus more efforts on highlighting and drawing attention to its own social responsibility through the website. In order to improve communication activities of JSC Concern Galnaftogaz on the Internet, it is necessary to improve its website, SEO and SMM strategies, advertising and communication strategies. In addition, the studied company needs to improve the usability of the site, increase its loading speed, introduce a calculator, and provide customers with the opportunity to make personalized orders. JSC Concern Galnaftogaz should also consider the possibility of creating blog and video content and setting up RSS. Improving the semantic core of the site and the position of the web page when searching on Google (leading to the first page) will help increase organic traffic and conversions. JSC Concern Galnaftogaz should also work on creating and constantly updating the content plan, increasing the number of subscribers in social networks, conducting an e-mail campaign with information reports, creating search ads and implementing targeted advertising and remarketing. It was determined that JSC Concern Galnaftogaz should consider directions for improving the marketing communications management system based on three blocks: marketing (competitive advantages of the brand, USP, measures to develop customer loyalty, differentiation from competitors), creative (brand book, design, rational and emotional elements of the brand, communication messages and methods of their transmission) and communication (promotion channels and means of communication on the Internet).